Moderating role of information system and mobile technology with learning and forgetting factors on organizational learning effectiveness - Kang H.; Turi J.A.; Bashir S.; Alam M.N.; Shah S.A. (Academic Press Inc., 2023)
Active learning, and forgetting, remain the norms of learning organizations. In this paper, the moderating role of information systems and mobile technology, with learning and forgetting factors, was assessed on organizational learning effectiveness. A mixed-method was adopted to comprehend the objectives of this study. In the first phase, interviews of the 19 experts were conducted to grasp the concept. In the 2nd phase, three (3) universities were visited, which have transformed their working and learning mechanism on information and communication system. In the third phase, quantitative data using the 5-Likert scale approach was collected from 187 state-owned and privately-owned universities registered with the Higher Education Commission (HEC) of Pakistan. The findings indicate that mobile technology and information systems play a significant moderating role in organizational learning effectiveness and development. The study recommends exploring further contextual factors of learning and forgetting and testing them with the latest technologies for learning development and exploration. Overall, this paper offers new insights into how information systems and mobile technology is contributing to organizational learning effectiveness with the contextual learning and forgetting factors by developing new institutional theory into the existing body of knowledge and by extending organizational theory and theory of socio-cognitive development. 2021 Elsevier Inc.